Germination of Phelipanche aegyptiaca and Cuscuta campestris seeds in composted farm manure. (June 2015) - Yaacoby, T.; Goldwasser, Y.; Paporish, A.; Rubin, B.
Abstract: The seed vitality of the parasitic weeds Phelipanche aegyptiaca (Egyptian broomrape) and Cuscuta campestris (field dodder) is a highly important factor in their dissemination to nearby and distant habitats. Fresh manure composting is an essential process as a 'good agricultural practice' of using manure safely as a fertilizer without dissemination of plant diseases, propagules or weed seeds. The aims of this research were a) to determine whether composting is effective in eliminating P. aegyptiaca and C. campestris seed vitality b) to evaluate the temperatures needed to eliminate seed viability of these species. Seeds of P. aegyptiaca and C. campestris were placed in various depths of compost piles and removed at different time intervals for germination rate determination. In a parallel experiment in the lab, P. aegyptiaca seeds were placed in incubators at fixed temperatures and removed periodically, to determine their germination rate. We found that ensuring compost temperatures above 55 °C for five to 6 h is sufficient to eradicate P. aegyptiaca seeds. This data was confirmed by the laboratory incubator experiments. Temperatures of 50–60 °C in the compost pile reduced C. campestris seed viability exponentially, but even 42 days of incubation did not completely eradicate their viability. Similar results were attained in a controlled temperature experiment in the laboratory, at which C. campestris seeds at 60 °C retained viability for 28 days. The results of this study stress the importance of maintaining high temperatures during manure composting procedures for eradication of P. aegyptiaca and C. campestris seeds and that. C. campestris seeds require a longer period of composting for eradication. Highlights: We examine Phelipanche aeg yptiaca and Cuscuta campestris seed vitality in compost. Experiments are conducted under lab and field conditions. Compost temperatures above 55 °C for 5–6 h eradicate P. aegyptiaca seeds. C. campestris seeds at 60 °C retain viability for 28 days. High compost temperatures are essential for parasitic plant seed eradication.